2020
DOI: 10.1021/acs.iecr.9b06064
|View full text |Cite
|
Sign up to set email alerts
|

Multiphase Viscoplastic Flows in a Nonuniform Hele-Shaw Cell: A Fluidic Device to Control Interfacial Patterns

Abstract: Inspired by the problem of the removal of in situ gel-like materials via a displacement flow process, we use a fluidic device known as Hele-Shaw cell to study the flow parameters related to the displacement flow efficiency. In a displacement flow process, when a less viscous fluid displaces a more viscous fluid, exotic interfacial patterns known as viscous fingering appear. Motivated by the recent developments in the literature, we experimentally study the effects of a simple cell nonuniformity with various ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 98 publications
1
8
0
Order By: Relevance
“… 120 This stabilization has been evidenced by Eslami et al (2020), where other fingering phases described as rough fingers are also shown. 121 …”
Section: Simulation Of Fluids In Porous Media At the Microscalementioning
confidence: 99%
“… 120 This stabilization has been evidenced by Eslami et al (2020), where other fingering phases described as rough fingers are also shown. 121 …”
Section: Simulation Of Fluids In Porous Media At the Microscalementioning
confidence: 99%
“…Since this experiment, numerous studies have been performed to generate further insight into how the taper angle influences viscous fingering [2,3,14,73,86,99]. Other popular physical alterations to the Hele-Shaw cell include uniformly separating the plates in time [43,44,83,100,122,133,143], rotating the entire Hele-Shaw cell at a given angular velocity [5,17,43,119], or replacing one of the plates with an elastic membrane [1,32,48,85,89,[108][109][110][111]. All of these configurations have been shown to produce patterns distinct from traditional Saffman-Taylor fingering.…”
Section: Introductionmentioning
confidence: 99%
“…Since this experiment, numerous studies have been performed to give further insight into how the taper angle influences viscous fingering [1,2,13,69,93]. Other popular physical alterations to the Hele-Shaw cell include uniformly separating the plates in time [42,78,94,116,127,135], rotating the entire Hele-Shaw cell at a given angular velocity [7,16,113], or replacing one of the plates with an elastic membrane [3,31,80,83,[102][103][104][105]. All of these configurations have been shown to produce patterns distinct from traditional Saffman-Taylor fingering.…”
Section: Introductionmentioning
confidence: 99%